Alumina reinforced zirconia implants: Effects of cyclic loading and abutment modification on fracture resistance. Issue 3 (March 2015) - Spies, Benedikt Christopher; Sauter, Carmen; Wolkewitz, Martin; Kohal, Ralf-Joachim
Abstract Objective The aim of the study was to evaluate the thermomechanical behavior of alumina-toughened zirconia (ATZ) oral implants in the artificial mouth and the fracture resistance (fracture load and bending moment) in a subsequent static fracture load test. The effects of abutment modification and different cyclic loadings were evaluated. Methods A total of 48 implants were used. 24 implants were left as machined (Group A), and 24 implants were shape modified at the abutment (Group B). Groups were divided into three subgroups composed of 8 samples each (A1/B1: no cyclic loading; A2/B2: 1.2 million cycles; A3/B3: 5 million cycles). Subsequently, all implants were statically loaded to the point of fracture. Results The implants showed the following survival rates after the artificial mouth: A2 and B2 100%; A3 and B3 87.5%. The following average fracture resistance values were found (fracture load [N]/bending moment [N mm]): A1 (583/2907), B1 (516/2825), A2 (618/2737), B2 (550/3150), A3 (802/3784) and B3 (722/3809). After 5 million loading cycles a significant increase in fracture load and bending moment was found. Modification of the abutment significantly decreased the fracture load of implants without foregoing dynamic loading. However, the shape modification altered the lever arm. For that reason, a smaller load resulted in the same bending moment. Therefore, abutment modification had no significant influence on the fracture resistance of ATZ. Significance Neither thermomechanical cycling in an aqueous environment nor modification of the abutment had a negative effect on the fracture resistance of ATZ.